SOCIO CULTURAL FACTORS INFLUENCING HOUSEWIVES' SHOPPING TENDENCIES ON TIKTOK SHOP (A STUDY OF SOCIAL STRUCTURE IN TERNATE CITY) - Maftuchatun Na'imah; Syahrir Ibnu; Jusan Hi Jusuf (Social Studies and Humanities Journal (SOSHUM), 2025)
This study aims to understand how socio-cultural factors influence the tendency of housewives to shop on TikTok Shop, using a case study in Makassar Barat Subdistrict, Ternate City. The research employed a descriptive qualitative method with a case study approach. Data were collected through participant observation, in-depth interviews, and documentation. The findings indicate that the consumption behavior of housewives is not solely influenced by economic factors but also by social and cultural structures that shape their perspectives on digital consumption. Using Anthony Giddens’ structuration theory, this behavior is understood as the result of a dialectical relationship between agency (housewives as social actors) and structure (digital media, social norms, and local economic policies). Furthermore, this study connects field findings with the context of regional policies that have not yet fully adapted to the development of the digital economy, as highlighted by Ibnu (2023) in Analysis of the Implementation of Regional Regulations Concerning Building Licenses. The research also expands the application of the social structuration approach in the digital context, as discussed by Ibnu (2024) in Exploring Political Socialization through the Lens of Giddens’ Structuration Theory. Thus, this study enriches the literature on digital anthropology and provides policy recommendations related to women’s household economic empowerment in the era of the digital creative economy.